Solar-Driven Remediation of Complex Cationic Dye Mixtures Using α-Fe2O3/ZnFe2O4 Heterocatalyst Under Sunlight: Insights from Single and Binary Systems - Rouibah, Karima; Bousba, Dalila; Akika, Fatima Zohra; Ferkous, Hana; Gouasmia, Abir; Benamira, Messaoud; Kucuk, Ilknur; Avramova, Ivalina; Lekmine, Sabrina; Odeibat, Hamza; Ola, Mohammad Shamsul; Amrane, Abdeltif; et al. (MDPI, 2026)
In the current investigation, the solar photocatalytic degradation of two cationic model dyes (methyl green (MG) and crystal violet (CV)) was studied using alpha-Fe2O3/ZnFe2O4 nanocomposite. The fine powder of nanoparticles was obtained by co-precipitation method at pH = 10 and characterized by X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and UV-vis spectroscopy. The surface properties were further examined through temperature-programmed desorption (TPD) and point of zero charge (PZC) measurements to assess the acid-base characteristics and surface charge behavior of the material. Adsorption and photocatalytic performance were systematically evaluated in both single and binary systems. Dark adsorption experiments showed a better affinity of the alpha-Fe2O3/ZnFe2O4 heterosystem towards MG dye in both cases. Under natural sunlight irradiation in the individual system, the photocatalytic activity of the nanoparticles was significantly higher for MG (81.67% removal) compared to CV (41.70%). Kinetics analysis revealed that the photodegradation of both dyes followed a pseudo-first-order model. In binary systems, competitive adsorption effects strongly influenced the degradation behavior, with MG showing preferential adsorption and higher degradation rates. Moreover, the MG discoloration kinetics followed a second-order model, while CV kinetics transitioned from second- to zero-order with increased initial concentration.
Keywords: solar photocatalysis; adsorption; alpha-Fe2O3/ZnFe2O4 nanoparticles; binary dye system; cationic dyes (methyl green, crystal violet); wastewater; PHOTOCATALYTIC DEGRADATION; AQUEOUS-SOLUTION; NANOPARTICLES; OPTIMIZATION; ZNFE2O4; Chemistry